Analisis Perilaku Siswa Kelas 5 SD N 4 Getassrabi Terhadap Game Online - Noor Fitriyani; Siti Masfuah; Wawan Shokib Rondli (WASIS : Jurnal Ilmiah Pendidikan, 2023)
This study aims to describe the reality of using online games in grade 5 students at SDN 4 Getassrabi and to analyze the behavior of grade 5 students at SDN 4 Getassrabi towards online games. In this study the authors apply a qualitative approach, because a qualitative approach produces a description of the people and behavior observed. This qualitative research will be carried out on informants or research subjects consisting of 3 grade 5 students, 3 parents of students, and a grade 5 teacher at SDN 4 Getassrabi. Data collection techniques include observation, interviews, and documentation. The data analysis technique used in this study went through 3 stages, namely: data reduction, data display, and verification or conclusion drawing. The results showed that the reality of using online games in grade 5 students at SDN 4 Getassrabi found that grade 5 students already knew and played online games. The types of online games that are popular are the types of war and battle. Meanwhile, the behavior of grade 5 students at SDN 4 Getassrabi when playing online games is more towards negative behavior, forms of negative behavior in children that arise when they play online games are in the form of defiance (negativism), aggression (aggression), disputes or quarrels (quarreling), and teasing.